1997
DOI: 10.1093/toxsci/35.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in the Splenotoxicity of Aniline

Abstract: Aniline-induced splenic toxicity is characterized by hemorrhage, capsular hyperplasia, fibrosis, and a variety of sarcomas in rats. Early biochemical events responsible for the observed effects are not known. To understand the mechanism(s) of aniline-induced splenic toxicity, single and multiple (four and seven) doses of 1 mmol/kg of aniline hydrochloride(AH) were given in rats. Apart from changes in the hematological parameters, these studies demonstrated that AH could induce lipid peroxidation and protein ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 11 publications
(13 reference statements)
2
19
1
3
Order By: Relevance
“…The choice of aniline dose was based on our earlier short-term studies that showed iron overload, and significant increases in lipid peroxidation, protein oxidation and DNA damage (oxidative stress) in the spleen (Khan et al, 1997a(Khan et al, , 2003bWu et al, 2005). Twenty four hours following the last dose, the animals were euthanized under nembutal (sodium pentobarbital) anesthesia and spleens were aseptically removed immediately, blotted, and weighed and then used for various analyses.…”
Section: Animals and Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The choice of aniline dose was based on our earlier short-term studies that showed iron overload, and significant increases in lipid peroxidation, protein oxidation and DNA damage (oxidative stress) in the spleen (Khan et al, 1997a(Khan et al, , 2003bWu et al, 2005). Twenty four hours following the last dose, the animals were euthanized under nembutal (sodium pentobarbital) anesthesia and spleens were aseptically removed immediately, blotted, and weighed and then used for various analyses.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…The toxicity is manifested by splenomegaly (Khan et al, 1997a(Khan et al, , 1999aCiccoli et al, 1999), elevated erythropoietic activity (Jenkins et al, 1972;Bus and Popp, 1987;Pauluhn, 2004), hyperpigmentation, hyperplasia, fibrosis (Bus and Popp, 1987;Khan et al, 1999aKhan et al, , 1999bKhan et al, , 2003a, and a variety of primary sarcomas after chronic exposure in rats (Goodman et al, 1984;Weinberger et al, 1985;Bus and Popp, 1987). Among various pathophysiological manifestations, fibrosis appears to be an important initiating preneoplastic lesion of the spleen (Khan et al, 1993(Khan et al, , 1995(Khan et al, , 1999a.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations